2001
DOI: 10.1055/s-2001-12437
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Dihydroxylation of C,C Double Bonds with Osmium Tetroxide Using Selenoxides as Co-oxidants

Abstract: Asymmetric dihydroxylation of olefins has been achieved in good yields and ee's using potassium osmate dihydrate (K 2 OsO 2 (OH) 4 , the pre-oxidant), (DHQD) 2 PHAL (the chiral ligand), potassium carbonate (the base) and selenoxides (the co-oxidants). Both the yield and the ee proved to be pH dependent, the highest yield and ee being found at almost the same pH values. The rate of the reaction was found to be highly dependent upon the structure of the selenoxide used. Some representative examples involving ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…In fact, it has been noted by Sharpless and co-workers that with carbamate nitrogen sources regioselectivity of the B isomer is inversely correlated with enantiselectivity 3a. We now report a method utilizing pH control to override other variables in the AA reaction of styrenes to selectively provide the B regioisomer with good enantiomeric ratios (ers) 1 …”
mentioning
confidence: 95%
“…In fact, it has been noted by Sharpless and co-workers that with carbamate nitrogen sources regioselectivity of the B isomer is inversely correlated with enantiselectivity 3a. We now report a method utilizing pH control to override other variables in the AA reaction of styrenes to selectively provide the B regioisomer with good enantiomeric ratios (ers) 1 …”
mentioning
confidence: 95%
“…We have previously reported highly enantioselective reactions of α-thio carbanions derived from benzyl phenyl and pyridyl sulfides, which were proven to proceed through different resolution pathways, i.e., dynamic kinetic resolution for the former carbanion and dynamic thermodynamic resolution for the latter. , These results showed that pivotal resolution pathways can be chosen by changing the substituent on the sulfur. Hoffmann and co-workers have reported that α-seleno carbanions are more configurationally stable than α-thio carbanions but less stable than α-oxy carbanions. , Since chiral selenides have the potential to be asymmetric catalysts , and synthetic intermediates, , it is important to develop the highly enantioselective reaction of α-seleno carbanions and to clarify the reaction pathways in more detail. , We now report enantioselective reactions of α-lithio benzyl phenyl selenide and α-lithio benzyl 2-pyridyl selenide with electrophiles in the presence of an external chiral ligand (Scheme ), including the reaction mechanism, on the basis of Beak's test using a deficient amount of the electrophile and the warm-cool procedure 14a-c together with the analysis of the data obtained by the MO calculation. We also report a highly enantioselective olefination involving the enantioselective reaction of the α-seleno carbanion with 4-substituted cyclohexanones and the subsequent stereospecific elimination reaction …”
Section: Introductionmentioning
confidence: 88%
“…Methyltrioxorhenium can be used in place of the flavin mimic [96], as can tungsten(VI) [97] and carbon dioxide [98]. Other alternatives for the oxidant for stoichiometric oxidations include the use of a selenoxide [99], including a photochemical oxidation of catalytic selenium [100], iodine [101], sodium chlorite [102], hypochlorite [103], and electrochemical methods [101,104]. Even air can be used as the oxidant [99,100], but care has to be taken with regard to the choice of solvent as cleavage of the product 1,2-diol can occur, especially when the alkene has an aryl substituent [53,105,106].…”
Section: Bisalkaloid Ligandsmentioning
confidence: 99%